The quality of outpatient services according to the perception of patients in Samutprakan Hospital - Anukulpipat, Praweena; Boonsanong, Kalaya; Sammawong, Kultida; Chaemchuen, Rawee; Pingsuthiwong, Sureerat (Samutprakan Hospital Journal (SMPK HOS J), 2023)
This research aims to survey the quality of outpatient services according to the perception of patients who received the service in Samutprakan Hospital. The data was collected from seven outpatient service departments as follows: 1) Department of Medicine, 2) Department of Surgery, 3) Department of Orthopedics, 4) Department of Gynecology, 5) Department of Obstetrics, 6) Department of Ophthalmology, and 7) Department of General Outpatients. 428 patients who received the service in seven outpatient departments were selected as the sample group by proportional to size. The quality service questionnaires were used to evaluate patients' perceptions, consisting of general information and the seven quality services. Descriptive statistics, t-tests, and ANOVA were used for data analysis. The results indicate that 1) The quality of outpatient services according to the perception of patients has an average value of 3.91 (S.D. = 0.69) and the Department of General Outpatients has the lowest average value of 3.69 (S.D. 0.82). 2) There was no statistical difference in the quality of the outpatient services according to age and medical benefits scheme. 3) Comparison of the service quality between the Department of General Outpatients and the Department of Gynecology were statistically significant differences in value. However, there was no statistical difference in the service quality of other departments.